Organic horticulture: a current demand, whose proper management is the only guarantee of safe food - Pinto Ferreira, Fernanda (2019)
The objective of this study was to evaluate the contamination by Escherichia coli in irrigation water and parasites in leafy vegetables cultivated in small organic horticultural properties and to investigate the critical points during cultivation. The study was carried out between July 2014 and May 2016 in 21 horticultural properties in the state of Paraná, Brazil. Two samples of leafy vegetables and one sample of irrigation water were collected per property. Water samples were analyzed by the chromogenic substrate technique to evaluate contamination by total coliforms and Escherichia coli, and the vegetables were evaluated by the techniques of Willis (1921), Hoffman et al. (1934) and Faust et al. (1939) for parasite contamination. The presence of E. coli was observed in 80.95% (17/21) of the water samples; with respect to vegetables, 45.23% (19/42) contained at least one parasite species, such as: hookworms, Chilomatix spp., Dipyllidium spp., Entamoeba spp., Strongyloides spp., Trichuris spp., nematode larva, non-sporulated oocyst. There was a statistical association between the fate of the sewage (dry sewage) and the positivity to the parasites. The data show fecal contamination in a significant number of samples and confirm the need for greater sanitary requirements during the cultivation of leafy vegetables, which are mostly consumed raw.